Palm oil diesel as a base fluid in formulating oil based drilling fluid - Md. Yassin, Abu Azam; Kamis, Azmi; Abdullah, Mohammad Omar (1991)

(untitled)
The usage of oil especially diesel oil as the continuous phase of drilling mud is widespread when drilling through sensitive producing formation and troublesome shale zone. Diesel oil is harmful to the environment, particularly marine environment during offshore drilling. Extensive legislation now exist in many countries to regulate this form of oil pollution. The used of palm oil derivatives could be considered as an alternative based fluid which is harmless to the environment. Tests have been undertaken to evaluate the characteristics of palm oil derivative as a base fluid in the oil base mud. The test results showed that palm oil derivative is suitable alternative to formulate oil based drilling mud with necessary rheological properties, compatible with existing mud additives and non-toxic to the marine life.